Pengaruh Takaran Biochar Sekam Padi dan Kompos Kotoran Ayam terhadap Pertumbuha dan Hasil Kubis Bunga (Brassica oleraceae, L.) - Theodorus Talo Mau; Eduardus Yosef Neonbeni (Savana Cendana, 2019)
Cabbage flower (Brassica oleracea, L.) or cauliflower is a vegetable commodity consumed by curd. This type of vegetable is very appreciated by the general public because it tastes good and delicious to make soup and also contains high nutrition. The purpose of this study was to determine the effect of biochar dosage of rice husk and compost of chicken manure on the growth and yield of flower cabbage. This research was carried out in August to October 2017, in the experimental garden of the Faculty of Agriculture, University of Timor, Sasi village, Kefamenanu city District, TTU Regency. Using a 3x3 factorial Randomized Block Design (RBD) repeated 3 times. The first factor was rice husk biochar consisting of 3 levels, namely without the use of biochar, biochar 2.5 t/ha, biochar 5 t/ha and the second factor was chicken manure compost consisting of three levels, namely without compost, 2.5 compost t/ha, compost 5 t/ha. The results showed that there was no interaction between parameters in both environmental parameters and yield parameters, but the administration of 5 t/ha biochar treatment and 5 t/ha chicken manure compost provided the best growth of flower cabbage plants.